Impaired Mycobacterium tuberculosis-specific T-cell memory phenotypes and functional profiles among adults with type 2 diabetes mellitus in Uganda - Ssekamatte, Phillip; Nabatanzi, Rose; Sitenda, Diana; Nakibuule, Marjorie; Bagaya, Bernard Ssentalo; Kibirige, Davis; Kyazze, Andrew Peter; Kateete, David Patrick; Sande, Obondo James; Crevel, Reinout van; Cose, Stephen; Biraro, Irene Andia (Frontiers in Immunology, 2024)
Background: Efforts to eradicate tuberculosis (TB) are threatened by diabetes mellitus (DM), which confers a 3-fold increase in the risk of TB disease. The changes in the memory phenotypes and functional profiles of Mycobacterium tuberculosis (Mtb)-specific T cells in latent TB infection (LTBI)-DM participants remain poorly characterised. We, therefore, assessed the effect of DM on T-cell phenotype and function in LTBI and DM clinical groups. Methods: We compared the memory phenotypes and function profiles of Mtb-specific CD4+ and CD8+ T cells among participants with LTBI-DM (n=21), LTBI-only (n=17) and DM-only (n=16). Peripheral blood mononuclear cells (PBMCs) were stimulated with early secretory antigenic 6 kDa (ESAT-6) and culture filtrate protein 10 (CFP-10) peptide pools or phytohemagglutinin (PHA). The memory phenotypes (CCR7/CD45RA), and functional profiles (HLA-DR, PD-1, CD107a, IFN-𝛾, IL-2, TNF, IL-13, IL-17A) of Mtb-specific CD4+ and CD8+ T cells were characterised by flow cytometry. Results: Naïve CD4+ T cells were significantly decreased in LTBI-DM compared to LTBI-only participants [0.47 (0.34-0.69) vs 0.91 (0.59-1.05); (p<0.001)]. Similarly, CD8+ HLA-DR expression was significantly decreased in LTBI-DM compared to LTBI-only participants [0.26 (0.19-0.33) vs 0.52 (0.40-0.64); (p<0.0001)], whereas CD4+ and CD8+ PD-1 expression was significantly upregulated in LTBI-DM compared to LTBI-only participants [0.61 (0.53-0.77) vs 0.19 (0.10-0.28); (p<0.0001) and 0.41 (0.37-0.56) vs 0.29 (0.17-0.42); (p=0.007)] respectively. CD4+ and CD8+ IFN-𝛾 production was significantly decreased in the LTBI-DM compared to the LTBI-only participants [0.28 (0.19-0.38) vs 0.39 (0.25-0.53); (p=0.030) and 0.36 (0.27-0.49) vs 0.55 (0.41-0.88); (p=0.016)] respectively. Additionally, CD4+ TNF and CD8+ IL-17A production were significantly decreased in participants with LTBI-DM compared to those with LTBI-only [0.38 (0.33-0.50) vs 0.62 (0.46-0.87); (p=0.004) and 0.29 (0.16-0.42) vs 0.47 (0.29-0.52); (0.017)] respectively. LTBI-DM participants had significantly lower dual-functional (IFN-𝛾+IL-2+ and IL-2+TNF+) and mono-functional (IFN-𝛾+ and TNF+ ) CD4+ responses than LTBI-only participants. Additionally, LTBI-DM participants had significantly decreased dual-functional (IFN-𝛾+IL-2+, IFN-𝛾+TNF+ and IL-2+TNF+) and mono-functional (IFN-𝛾+, IL-2+ and TNF+ ) central and effector memory CD4+ responses compared to LTBI-only participants. Conclusion: Type 2 DM impairs the memory phenotypes and functional profiles of Mtb-specific CD4+ and CD8+ T cells, potentially indicating underlying immunopathology towards increased active TB disease risk.